Interações contingentes em ambientes virtuais de aprendizagem - David, Priscila Barros (2010)
The purpose of this research is to develop an analytical system to understand the interactions in a LMS that promote learning (contingent interactions). The LMS are a class of software for the design, suport and management of Internet-based courses. Integrate Information and Communication Technologies in order to create an environment that enables the process of interaction and production of knowledge by participants of the educational scene. This study investigated the concept of contingent interaction in the context of two undergraduate courses, taught at the blended mode within the Open University of Brazil (UAB), which are linked to different areas of knowledge (hard and humanity sciences) and were ministered for different audiences. As part of the methodology, the exchange of messages between the participants of the research through discussion foruns and chats was observed and analyzed according to the typical parameters of contingent interactions. The analysis of the messages was compared with data obtained from semi-structured interviews conducted with some students and their tutors. The development of the Analytical System of Contingent Interaction integrated different theoretical fields (Education, Psychology and Linguistics) that point out the interaction as an essential phenomenon in educational situations. The categories were builded based on the literature that discusses the concept of interaction, and applied to both synchronous and asynchronous communication established between the interlocutors of the hard and humanity courses. The resulting analytical system is structured into four general categories (Conversation, Textualization, Dialogue and Learning) and some sub-categories, linked to the theoretical areas that supported its development. The results show up the internal coherence of the system and its validity, confirming the existence of contingent interaction characteristics in all contexts examined, which also enables the system application to other research universes. The Analytical System of Contingent Interactions presents theoretical and empirical contributions to the concept of contingent interaction, and provide parameters for performing actions in Distance Education based on a social interactionist perspective. The research indicates that the emergence of interactions with learning objectives depends far more on the relations established among people involved in the educational act than on a specific area or communication tool.